2008
DOI: 10.1002/cpp.577
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation as mediator of treatment outcome in therapy for deliberate self‐harm

Abstract: This study presents the outcomes of mediator analyses as part of a randomized controlled trial of Cognitive-Behavioural Therapy (CBT) for young people who engage in deliberate self-harm (DSH). The study involved 90 people, aged 15-35 years, who were randomly assigned to CBT in addition to treatment as usual or to treatment as usual only. The fi ndings showed that changes in DSH were partially mediated by changes in emotion-regulation diffi culties, particularly diffi culties with impulse control and goal-direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 29 publications
6
66
0
Order By: Relevance
“…The relevance to increase self-efficacy and mentalizing is supported by psychotherapy studies reporting self-efficacy and aspects of mentalization to be mediators of the outcome [38,39]. Yet, a recent review reported that there are specific conditions self-efficacy is not beneficial for and that working on self-efficacy in psychotherapy might not always be necessary [40].…”
Section: Discussionmentioning
confidence: 95%
“…The relevance to increase self-efficacy and mentalizing is supported by psychotherapy studies reporting self-efficacy and aspects of mentalization to be mediators of the outcome [38,39]. Yet, a recent review reported that there are specific conditions self-efficacy is not beneficial for and that working on self-efficacy in psychotherapy might not always be necessary [40].…”
Section: Discussionmentioning
confidence: 95%
“…Emotion regulation difficulties have been conceptualized as a relatively distinct feature of the consequences of childhood abuse that are supposed to derive from the abuse's disruptive impact on the achievement of the developmental goals and interpersonal relatedness (Van der Kolk, 1996;Slee et al, 2008b). To influence the vulnerabilities in emotion regulation, the CBT intervention aimed to enhance emotional awareness, distress tolerance and problem solving skills (Slee et al, 2008c). These interventions require a good therapeutic alliance around trust and safety and sufficient time for the internalization of emotional control to develop.…”
Section: Discussionmentioning
confidence: 99%
“…Recently a focus has been placed on the importance of emotion regulation in anxiety as well (Hannesdottir and Ollendick 2007;Mennin 2006;Trosper et al 2009). Preliminary research suggests that considering this affective component also aids in therapy (Hinton et al 2009;Slee et al 2008).…”
Section: Implications For Practice and Directions For Future Researchmentioning
confidence: 97%